3D Cold‐Trap Environment Printing for Long‐Cycle Aqueous Zn‐Ion Batteries (Adv. Mater. 9/2023). Issue 9 (2nd March 2023) - Lu, Hongyu; Hu, Jisong; Zhang, Yan; Zhang, Kaiqi; Yan, Xiaoying; Li, Heqi; Li, Jianzhu; Li, Yujie; Zhao, Jingxin; Xu, Bingang
Abstract : Aerogel Anodes An innovative 3D cold trap environment printing (3DCEP) technology is proposed by Yujie Li, Jingxin Zhao, Bingang Xu, and co‐workers in article number 2209886 to fabricate a highly aligned aerogel anode with MXene and Zn powder (3DCEP‐MXene/Zn–P). Benefitting from the combined induction of laminar flow and ice crystals in the 3DCEP process, MXene and Zn–P can be arranged in the Zn anode to achieve a unique Zn‐dendrite inhibition effect.